Dipolaritons in quantum dots (2015)
Abstract. Dipolaritons are quasiparticles that arise in coupled quantum wells embedded in a microcavity, they are a superposition of a photon, a direct exciton and an indirect exciton. An interesting feature of dipolaritons is that their excitons can carry an electric dipole moment. Previous works have found this kind of system suitable for terahertz lasing (Phys. Rev. A 89, 023836) and Bose-Einstein condensation (Phys. Rev. B 90, 125314). In this thesis we study a system that consists of two interacting quantum dots embedded in a microcavity, from the point of view of dipolaritons in direct analogy with the quantum well case. A constant magnetic field is also taken into account. First, the zero temperature case is studied with an exact diagonalization of a finite system hamiltonian in order to find the effects of the magnetic field on the properties of direct and indirect excitons, including their statistics. Then we include light and investigate the properties of a single dipolariton. Next, a variational approach is used to study the many-body problem and we find the effects of the magnetic field on the ground state energy and number of photons. Finally, we consider the problem at finite temperatures and use a self-consistent procedure in a Hartree-Fock-Bogoliubov approximation to find the effect of the magnetic field on the critical temperature for Bose-Einstein condensation.